'First in Family' University Graduates in England - Morag Henderson; Nikki Shure; Anna Adamecz-Völgyi (Institute of Labor Economics (IZA), 2019)
Universities around the world are attempting to increase the diversity of their student population. This includes individuals who are 'first in family' (FiF), those who achieve a university degree, but whose (step) parents did not. We provide the first large scale, quantitative evidence on FiF graduates in England using a nationally representative survey linked to administrative education data. We find that FiF young people make up 18 percent of a recent cohort, comprising nearly two-thirds of all university graduates. Comparing individuals with no parental higher education we show that ethnic minorities and those with higher levels of prior attainment are more likely to experience intergenerational educational mobility and become a FiF. Once at university, those who are FiF are more likely to study Law, Economics and Management and less likely to study other Social Sciences, Arts and Humanities than students whose parents are university graduates. We also find evidence that FiF students are less likely to graduate from elite universities and have a higher probability of dropping out, even after prior educational attainment, individual characteristics and socio-economic status are taken into account.
Keywords: I21; I23; I24; 330; higher education; widening participation; university access; dropout; intergenerational educational mobility